2022
DOI: 10.3390/pharmaceutics14010171
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines—Are They Effective and Safe during Pregnancy?

Abstract: Since the teratogenicity of Thalidomide has been proven, herbal products are more commonly used in pregnancy to not only relieve morning sickness but also to fight infections. These products are frequently considered as natural and therefore harmless. However, herbs contain a number of active substances that, when used during pregnancy, can affect the development of the fetus. Often, pregnant women do not consult the usage of herbal medicines with a physician. The access to these products is easy and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 110 publications
1
23
0
1
Order By: Relevance
“…Our study subjects revealed that they had been using ginger tea to treat morning sickness, cough, and to aid digestion; sniffing or drinking the exudate of dama-kesse to treat headache, fever, flank pain, and hypertension; and garlic for common cold, flu, and prevention of preeclampsia. Their uses are supported by traditional claims of the plants as well as in vivo and in vitro experimental studies [ 10 , 13 , [35] , [36] , [37] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study subjects revealed that they had been using ginger tea to treat morning sickness, cough, and to aid digestion; sniffing or drinking the exudate of dama-kesse to treat headache, fever, flank pain, and hypertension; and garlic for common cold, flu, and prevention of preeclampsia. Their uses are supported by traditional claims of the plants as well as in vivo and in vitro experimental studies [ 10 , 13 , [35] , [36] , [37] ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study from Pakistan, pregnant women who want to end their pregnancies take 2 g of ginger daily [ 9 ]. Regarding other herbs, the available data are often heterogeneous and show conflicting results without a clear conclusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cranberry is a plant from the family Ericaceae, known as V. macrocarpon. It was used by native Americans to treat infections [41]. Other varieties, including V. oxycoccos, a small/bog cranberry, and V. erythrocarpum, a southern mountain cranberry, have also been used to treat UTI because these berries contain many biologically active compounds that are supposed to be responsible for anti-uropathogenic activities [42].…”
Section: Vaccinium Macrocarpon-cranberrymentioning
confidence: 99%
“…Use of cranberry products during pregnancy appears to be safe. 52 In the Norwegian Mother and Child Cohort Study the use of cranberry products was not found to be harmful during pregnancy. 53 …”
Section: Discussionmentioning
confidence: 99%